2021
DOI: 10.1038/s41598-021-01007-w
|View full text |Cite
|
Sign up to set email alerts
|

Differential urine proteome analysis of a ventilator-induced lung injury rat model by label-free quantitative and parallel reaction monitoring proteomics

Abstract: Urine is a promising resource for biomarker research. Therefore, the purpose of this study was to investigate potential urinary biomarkers to monitor the disease activity of ventilator-induced lung injury (VILI). In the discovery phase, a label-free data-dependent acquisition (DDA) quantitative proteomics method was used to profile the urinary proteomes of VILI rats. For further validation, the differential proteins were verified by parallel reaction monitoring (PRM)-targeted quantitative proteomics. In total,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The peptide samples were analyzed using the Orbitrap Fusion Lumos Tribrid mass spectrometer coupled with EASY-nLC 1000 HPLC system (Thermo Scientific, Germany) as described previously (Qin et al 2021 ; Sun et al 2022 ). Briefly, the digested peptides were loaded onto a C18 trap column (3 µm, 75 µm × 2 cm, 100 A°) and then transferred to a C18 reversed-phase analytical column (2 µm, 50 µm × 250 mm, 100 A°).…”
Section: Methodsmentioning
confidence: 99%
“…The peptide samples were analyzed using the Orbitrap Fusion Lumos Tribrid mass spectrometer coupled with EASY-nLC 1000 HPLC system (Thermo Scientific, Germany) as described previously (Qin et al 2021 ; Sun et al 2022 ). Briefly, the digested peptides were loaded onto a C18 trap column (3 µm, 75 µm × 2 cm, 100 A°) and then transferred to a C18 reversed-phase analytical column (2 µm, 50 µm × 250 mm, 100 A°).…”
Section: Methodsmentioning
confidence: 99%
“…An Orbitrap Fusion Lumos Tribrid mass spectrometer coupled with an EASY-nLC 1000 HPLC system (Thermo Scientific, Germany) was used to analyze the peptide sample, as previously described 15 , 16 . In detail, the digested peptides were loaded onto a trap column (75 µm × 2 cm, 3 µm, C18, 100 A°), and then transferred to a reversed-phase analytical column (50 µm × 250 mm, 2 µm, C18, 100 A°).…”
Section: Methodsmentioning
confidence: 99%
“…The raw data files were processed using Progenesis QIP and Mascot software, as previously described 16 . Briefly, the search parameters were set as follows: SwissProt Rattus database (containing 8086 sequences), trypsin digestion, parent ion mass tolerance of 10 ppm, fragment ion mass tolerance of 0.02 Da, fixed modification of carbamidomethylated cysteine (+ 58.00 Da); variable modifications of deamidated glutamine asparagine (+ 0.984 Da) and oxidized methionine (+ 15.995 Da).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the urinary system, biomarkers in urine can be a sensitive indicator of respiratory diseases. Urine proteomic studies have identified biomarkers for several respiratory diseases, such as lung cancer 87 , pulmonary fibrosis, 88 ventilator-induced lung injury, 89 and acute respiratory distress syndrome (ARDS). 90 Therefore, urine is a promising resource for studying biomarkers of lung diseases.…”
Section: Proteomics Of Copdmentioning
confidence: 99%